Information Literacy Programme in the Federal University of Technology Akure, Nigeria: An Evaluation - Abiolu, Oluremi Adenike; Okere, Oluchi Ojinamma (MiddleBelt Journal of Library and Information Science, 2016)
Evaluation of academic programmes is an important aspect of instructional design. This study assesses the perceptions of the students of the Federal University of Technology Akure, Nigeria on the availability of the factors that support effective implementation of GNS 103: Information Retrieval - the IL programme. The stratified random sampling technique was used to draw a sample of six hundred first year students of the 2012/2013 academic session, who were issued the questionnaire to test a number of factors required for effective implementation of the programme in the University. Descriptive statistics were used to analyse the data. The findings indicated that timing factors were good but that a separate hour for tutorials was required; course delivery received a generally approving pattern. Lecturers were regular (72%), punctual (66%), and proficient in their delivery of the course (53%). The content of the course was seen as good but weak in practical, library tour and ICT. IL enjoys support in terms of functional writing boards (62%), and neat learning environment but suffers: lack of public address system (81.6%), poor lighting (67.8%) and ventilation (61.9%) conditions, insufficient space for students (67.9%), no designated lecture room (66.3%) and no course book was available (70.0%). The University should upgrade the facilities used in running the programme. Also, those responsible for the academic content of the course should provide relevant course book and improve ICT component of the programme by providing computer (online) facilities to enhance practical knowledge. Lecturers of the course should be trained on pedagogy for effective delivery of learning.